Comparative study on electroencephalography characteristics of professional and non-professional drivers in tunnel sections: A field investigation. - Yang, Yongzheng; Du, Zhigang; Jiang, Zehao (Work, 2024)
BACKGROUND: The tunnel section is a complex traffic scenario and an accident prone area. There are differences in the performance of different driving groups in tunnel environments, which may have an impact on traffic safety. OBJECTIVE: To study the differences in the impact of tunnel environment on professional and non-professional drivers. METHODS: Based on the vehicle experimental data, the electroencephalography (EEG) power was compared for professional and non-professional drivers. The impact of illumination changes and longitudinal slope on different driving groups was analyzed. RESULTS: At tunnel entrance with severely reduced lighting, the adaptation time of non-professional drivers to the light environment is 1.5 times that of professional drivers. When driving on the longitudinal slope, professional drivers perform better. The greater the longitudinal slope, the more obvious the advantages of professional drivers. However, in areas with relatively good traffic conditions, professional drivers are more prone to be distracted. CONCLUSION: Professional and non-professional drivers have their own advantages and disadvantages in the tunnel environment. In general, the driving adaptability of professional drivers is better than that of non-professional drivers in tunnel sections. The research conclusions provide a reference for driver safety training.